KAJIAN DAMPAK PENGEMBANGAN PARIWISATA TERHADAP PENDAPATANASLI DAERAH DAN SOSIAL EKONOMI MASYARAKAT - Sutarmin; Yulis Maulidia Bernis; Aqib Ardiansyah; Kurniawan (JURNAL ILMIAH ULTRAS BREBES, 2018)
The tourism sector is one sector that has a multiplier effect on the economic growth of a region.One area that is aware of the importance and strategic of the tourism sector is Brebes Regency.Although it has a lot of potential and interesting, the tourism potential in Brebes has notcontributed Locally-generated revenue (PAD) as expected. Required research that aims to (1)know the impact of tourism development on socio-economic society; (2) to know the impact oftourism development on Locally-generated revenue (PAD) of Brebes Regency; (3) to know thepotential of tourism market; (4) to know the level of tourism visitors absorption and (5) to knowalternative of tourism development strategy in Brebes Regency. Data collection method of thisresearch is through literature study, interview and observation. The results of this study are: (1)For ease of development, Brebes Regency is divided into 3 tourism zones, which is the 1sttourism zone (North Brebes) focusing on marine tourism theme, 2nd tourism zone (CentralBrebes) focusing on adventure tourism and zone 3 (South Brebes) that focus on resting; (2) Tokeep pace, the tourism sector of Brebes Regency must grow exponentially through variousstrategic breakthroughs. Strategic breakthroughs that can be done by Brebes Local Governmentinclude (a) ticket price adjustment, (b) change of manager from Pemda to Perusda or purelyprivate (c) tax imposition on tourism object not managed by local government (d) adding newtourism object with various interesting themes.